Case report: Constrictive pericarditis after coronary artery perforation during percutaneous coronary intervention - Kim, Kyung An; Lee, Kwan Yong; Hwang, Byung-Hee; Kim, Do Yeon; Park, Chan Beom (Frontiers in Cardiovascular Medicine, 2023)
A 77-year-old man underwent percutaneous coronary intervention (PCI) at the right coronary artery, which was complicated by coronary artery perforation (CAP). After prolonged balloon tamponade proximal to the CAP there was no more contrast extravasation, and the CAP was thought to have resolved. Computed tomography (CT) and echocardiography the following day did not find evidence of continued bleeding, and the patient was discharged. Echocardiograms and chest CT scans obtained one week and two months after PCI detected no remarkable interval change. The patient complained of progressive dyspnea and abdominal distension seven months after PCI however, and echocardiography found an increased amount of pericardial effusion and constrictive physiology. The patient underwent pericardiectomy due to congestive hepatopathy, and progressive dyspnea. The pericardium was thickened and adhesive, and a dark bloody effusion was found. Pathology was unremarkable except for thick fibrosis. After the operation the patient made full recovery, and is stable three years after surgery.